Retail Banking Service Quality and Customer Loyalty: The Role of Trust and Commitment as Mediators - Redda, Ephrem Habtemichael; Van Deventer, Marko (International Review of Management and Marketing, 2023)
This research examines how service quality, trust, commitment, and loyalty are related in retail banking. The study proposes a model that includes trust and commitment as mediating factors between service quality, and bank loyalty. The researchers collected data from 271 participants and used a descriptive design and quantitative approach to analyse the data. The study utilized the PROCESS macro-Version 3.5 to conduct the mediation analysis. The results indicate that service quality in retail banking has a positive impact on customer trust and commitment, which, in turn, predict customer loyalty. The mediation analysis reveals that trust and commitment play a significant role in mediating the relationship between service quality and customer loyalty. Since the direct effect of service quality on loyalty remained significant after the intervention/mediation of trust and commitment in the model, the mediation is interpreted as partial mediation. Findings of the study do provide a marketing guide to banking professionals who design and implement banking solutions in the retail banking environment.